PL3 Amidase, a Tailor-made Lysin Constructed by Domain Shuﬄing with Potent Killing Activity against Pneumococci and Related Species - Blázquez, Blas; Fresco-Taboada, Alba; Iglesias-Bexiga, Manuel; Menéndez, Margarita; García, Pedro (Frontiers in Microbiology, 2016)
The emergence and spread of antibiotic-resistant bacteria is pushing the need of alternative treatments. In this context, phage therapy is already a reality to successfully fight certain multiresistant bacteria. Among different phage gene products, murein hydrolases responsible of phage progeny liberation (also called lysins or endolysins) are weapons that target specific peptidoglycan bonds, leading to lysis and death of susceptible bacteria when added from the outside. In the pneumococcal system, all but one phage murein hydrolases reported to date share a choline-binding domain that recognizes cell walls containing choline residues in the (lipo)teichoic acids. Some purified pneumococcal or phage murein hydrolases, as well as several chimeric proteins combining natural catalytic and cell wall-binding domains have been used as effective antimicrobials. In this work we have constructed a novel chimeric N-acetylmuramoyl-L-alanine amidase (PL3) by fusing the catalytic domain of the Pal amidase (a phage-coded endolysin) to the cell wall-binding domain of the LytA amidase, the major pneumococcal autolysin. The physicochemical properties of PL3 and the bacteriolytic effect against several pneumococci (including 48 multiresistant representative strain) and related species, like Streptococcus pseudopneumoniae, Streptococcus mitis and Streptococcus oralis, have been studied. Results have shown that low doses of PL3, in the range of 0.5–5 µg/ml, are enough to practically sterilize all choline-containing strains tested. Moreover, a single 20-µg dose of PL3 fully protected zebrafish embryos from infection by S. pneumoniae D39 strain. Importantly, PL3 keeps 95% enzymatic activity after four weeks at 37ºC and can be lyophilized without losing activity, demonstrating a remarkable robustness. Such stability, together with a prominent efficacy against a narrow spectrum of human pathogens, confers to PL3 the characteristic to be an effective therapeutic. In addition, our results demonstrate that the structure/function-based domain shuffling approach is a successful method to construct tailor-made endolysins with higher bactericidal activities than their parental enzymes.